Efek Mediasi Kepuasan Kerja pada Pengaruh Motivasi Dan Kemampuan Kerja Terhadap Kinerja Pegawai - Muskadi Sembiring; Jufrizen Jufrizen; Hasrudy Tanjung (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
This study aims to analyze the effect of motivation and ability, analyze the effect of motivation and work ability on employee performance, analyze the effect of job satisfaction on employee performance and to analyze whether job satisfaction is a mediating variable between motivation and work ability on performance at the Financial Management Agency and Regency Assets Deli Serdang. The population of this study were all employees of the Deli Serdang Regency's Financial and Asset Management Agency, amounting to 60 people. The data collection method used was a questionnaire. Data analysis techniques using PLS-SEM. The results showed that directly, work motivation had a positive and significant effect on employee job satisfaction, work ability had a negative and not significant effect on employee job satisfaction, work motivation had a positive and significant effect on employee performance, work ability had a positive and significant effect on employee performance, satisfaction work has a positive and not significant effect on employee performance. Indirectly, job satisfaction does not mediate the relationship between motivation variables with employee performance variables